Influence of finned charges on melting process performance in a thermal energy storage; Thermal Science and Engineering Progress; Vol. 37 - Izadi M. Mohsen; Fagehi H. Hassan; Imanzadeh A. Amir; Altnji S. Sam; Hamida M. B. B. Mohamed Bechir Ben; Sheremet M. A. Mikhail Aleksandrovich (2023, 2023)
Title screen